2015
DOI: 10.1155/2016/3578368
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Shiga Toxin Production by Enterohemorrhagic Escherichia coli

Abstract: Virulence of enterohemorrhagic Escherichia coli (EHEC) strains depends on production of Shiga toxins. These toxins are encoded in genomes of lambdoid bacteriophages (Shiga toxin-converting phages), present in EHEC cells as prophages. The genes coding for Shiga toxins are silent in lysogenic bacteria, and prophage induction is necessary for their efficient expression and toxin production. Under laboratory conditions, treatment with UV light or antibiotics interfering with DNA replication are commonly used to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 40 publications
0
47
0
Order By: Relevance
“…Previously, we reported that H 2 O 2 also induced ArtAB production in S. Typhimurium DT104 [9]. [15,16,[31][32][33]. In E. coli treated with H 2 O 2 , only a very small fraction of cells is induced for prophage excision and subsequent lytic development, compared to cells treated with MTC [15,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we reported that H 2 O 2 also induced ArtAB production in S. Typhimurium DT104 [9]. [15,16,[31][32][33]. In E. coli treated with H 2 O 2 , only a very small fraction of cells is induced for prophage excision and subsequent lytic development, compared to cells treated with MTC [15,31].…”
Section: Discussionmentioning
confidence: 99%
“…Absence of cI leads to the expression of the anti-terminators Q. The protein Q allows read-through of terminators that inhibit transcription of late phage genes, including stxAB, which is located between Q and Holin genes [15,28]. The ArtAB-encoding genes of S. Typhimurium DT104 strain U1 and S. Worthington strain 182 share the location of stx2 within a functional prophage (Y. Tamamura, I. Uchida, M. Akiba and M. Kusumoto, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under such conditions, the RecA protein recognizes bacterial single-stranded DNA fragments and is activated to stimulate the self-cleavage of the cI repressor. This leads to initiation of phage lytic cycle through transcription from the early p L and p R promoters (Łoś et al, 2009;Węgrzyn et al, 2012;Szych et al, 2013;Licznerska et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Enterohemorrhagic E. coli (EHEC) is a pathogenic E. coli line capable of causing disease in humans and is responsible for a large number of food-borne diseases associated with outbreaks of bloody diarrhea, which may be complicated by the development of hemolytic uremic syndrome (HUS) (Jost, Bidet, Carrère, Kurkdjian, & Bonacorsi, 2016). Antimicrobial therapy is not recommended during EHEC infection because of the risk of developing HUS through the induction and/or production of Shiga toxin, the main virulence factor of EHEC (Licznerska, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%